Susceptibility-Based Differentiation of Intracranial Calcification and Hemorrhage in Pediatric Patients. (July 2015) - Gumus, Kazim; Koc, Gonca; Doganay, Selim; Gorkem, Sureyya B.; Dogan, Mehmet S.; Canpolat, Mehmet; Coskun, Abdulhakim; Bilgen, Mehmet
Differential diagnosis of intracranial hemorrhage versus calcification on conventional magnetic resonance images (MRIs) is often challenging. Although computed tomography (CT) confirms calcification, phase information obtained during susceptibility-weighted imaging can be useful in distinguishing between 2 pathologies. Fourteen patients previously diagnosed to have hemorrhage or calcification with imaging were included in the study retrospectively. Phase shift values of hemorrhage and calcification were compared by using Student t test. The pathologies identified were tuberous sclerosis, Sturge-Weber syndrome, craniopharyngioma, congenital cytomegalovirus, subependymal hemorrhages, and hemorrhagic microembolic infarction. Calcifications appeared hypointense whereas hemorrhages were hyperintense on phase maps (left-handed magnetic resonance system). Statistical comparison of phase shift values yielded significant difference between hemorrhage versus calcification ( P < .01). Phase maps were found to offer valuable data to differentiate 2 pathologies when used complementary to conventional magnetic resonance images. Considering the relatively higher risks of radiation exposure in children, susceptibility-weighted imaging with phase maps may help to waive radiation exposure from CT.